Effect of Catalytic Gasification of Active Carbon from Plum Stones on its Mesoporous Structure - R. Leboda; W. Grzegorczyk; A. Lodyga; A. Dabrowski (Adsorption Science & Technology)
The possibilities of the development of a mesoporous structure during gasification of carbonaceous material with water vapour in the presence of a calcium(II) catalyst are demonstrated. Investigations have been carried out on active carbon prepared from plum stones. For comparison, the same experiments in the absence of the catalyst were also made. The characteristics of the micro- and meso-porous structures of the adsorbents have been determined from the adsorption–desorption isotherms of nitrogen. The data have been submitted to treatment from the BET, Harkins–Jura, Sing as well as Derjaguin, Broeckhoff, de Boer and Dubinin equations. The texture of the adsorbent particles has been studied by means of scanning electron microscopy. The kinetics of gasification of the carbon adsorbent in the presence and absence of catalyst has also been studied. In addition, samples of the prepared carbon adsorbents were examined by X-ray diffraction.